2011
DOI: 10.1007/s10008-011-1477-6
|View full text |Cite
|
Sign up to set email alerts
|

Numerical investigations of solution resistance effects on nonlinear electrochemical impedance spectra

Abstract: The effect of solution resistance on the nonlinear electrochemical impedance spectra under quasi-potentiostatic conditions was investigated by numerical simulations. An electron transfer reaction, a reaction with an adsorbed intermediate and a reaction exhibiting negative resistance were chosen as the candidates and large amplitude perturbations were employed. The potential across the interface drifts initially and stabilizes after a certain time, which depends on the solution resistance and the kinetic parame… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 47 publications
0
5
0
Order By: Relevance
“…When mass transfer is rapid but R sol is not negligible, the governing equations can be solved numerically to calculate the impedance spectra at any frequency. [43][44][45][46] Kramers Kronig Transforms (KKT) are mathematical equations that can be used to confirm that the response arise from a system which is linear, causal and stable. While KKT are successful in flagging violations of stability, 47 they are only partially successful in identifying nonlinearity effects.…”
Section: Nl-cpementioning
confidence: 99%
See 3 more Smart Citations
“…When mass transfer is rapid but R sol is not negligible, the governing equations can be solved numerically to calculate the impedance spectra at any frequency. [43][44][45][46] Kramers Kronig Transforms (KKT) are mathematical equations that can be used to confirm that the response arise from a system which is linear, causal and stable. While KKT are successful in flagging violations of stability, 47 they are only partially successful in identifying nonlinearity effects.…”
Section: Nl-cpementioning
confidence: 99%
“…21 If the impedance is acquired under pseudo potentiostatic conditions, when R sol is significant and perturbation amplitude is large, the potential drop across electrode-electroyte interface will not be sinusoidal even if the potential applied across the entire system is sinusoidal. [13][14][15]46 Initially, it was though that R p,NL in these cases will always decrease with E ac0 , but it was later shown that R p,NL may increase or decrease with E ac0 depending on the value of bias potential (E dc ) and R sol . [13][14][15] Expressions were also derived for R p,NL for electrochemical reactions obeying Tafel, or Butler Volmer or Nernst law or an electron transfer reaction coupled with electrochemical adsorption reaction (E-EAR), when NLEIS was measured under potentiostatic or galvanostatic conditions.. [13][14][15] In corrosion studies, it is desirable to measure the linear polarization resistance (R p ) quickly and independently of polarization experiments.…”
Section: Nl-cpementioning
confidence: 99%
See 2 more Smart Citations
“…9 must be used along with the other equations to simulate the impedance spectra. In these cases, upon applying the ac potential, the systems takes some time to yield steady periodic current (18). The simulations were performed such that sufficient wait time was given to achieve steady periodic current at each frequency and the data collected subsequently was analyzed.…”
Section: Solution Resistancementioning
confidence: 99%